2007
DOI: 10.1007/s11738-007-0103-9
|View full text |Cite
|
Sign up to set email alerts
|

Response of cytokinin pool and cytokinin oxidase/dehydrogenase activity to abscisic acid exhibits organ specificity in peas

Abstract: Changes in cytokinin pool and cytokinin oxidase/dehydrogenase activity (CKX EC: 1.5.99.12) in response to increasing abscisic acid (ABA) concentrations (0.5-10 lM) were assessed in the last fully expanded leaves and secondary roots of two pea (Pisum sativum) varieties with different vegetation periods. Certain organ diversity in CKX response to exogenous ABA was observed. Treatment provoked altered cytokinin pool in the aboveground parts of both studied cultivars. Specific CKX activity was influenced significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
1
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
2
1
0
1
Order By: Relevance
“…On the other hand, the repression of CK metabolic genes by exogenous ABA treatment (Figure 6) suggests that the stress-induced ABA accumulation might also play a role in the downregulation of CK levels by stresses. In agreement with our observation, it was reported that treatment of plants with exogenous ABA decreased CK contents (Vaseva et al, 2008). Therefore, the ABA: CK ratio changed by stresses in favor of ABA may facilitate plant adaptation to adverse environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the repression of CK metabolic genes by exogenous ABA treatment (Figure 6) suggests that the stress-induced ABA accumulation might also play a role in the downregulation of CK levels by stresses. In agreement with our observation, it was reported that treatment of plants with exogenous ABA decreased CK contents (Vaseva et al, 2008). Therefore, the ABA: CK ratio changed by stresses in favor of ABA may facilitate plant adaptation to adverse environmental conditions.…”
Section: Discussionsupporting
confidence: 93%
“…However, unlike PBZ and ethrel application, ABA application strongly inhibited IP content from 14 DAT ( Figure 2 ), suggesting that the promotion of bulblet development by ABA is not due to the increase in CK content. In previous studies, ABA was proven to suppress both the content and signaling of CK in plants ( Vaseva et al, 2008 ; Nishiyama et al, 2011 ; Takatsuka and Umeda, 2019 ), which agreed with our observation.…”
Section: Discussionsupporting
confidence: 92%
“…We have shown that HB expression in the apex correlates with the WUS expression and CK response decline ( Merelo et al 2022 ). It has been proposed that elevated ABA levels, as induced by drought, could inhibit the biosynthesis of CK and therefore the CK responses ( Abe et al 1997 ; Vaseva et al 2008 ). Then, the ABA accumulation activated by the HB gene expression could participate in the progressive repression of the CK response observed at the end of flowering ( Merelo et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%